2015
DOI: 10.1007/s11916-015-0503-2
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Head Pain

Abstract: Muscle nociception is mainly characterized by local tenderness and referred pain. The neurophysiological basis of muscle pain supports a role of sensitization mechanisms. From a clinical viewpoint, muscle pain is represented by the presence of myofascial trigger points (TrPs). Evidence suggests that TrPs are able to start a peripheral nociceptive mechanism and hence contributing to changes in the central nervous system. Several studies demonstrated that the referred pain elicited by TrPs reproduces the headach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 63 publications
1
45
0
2
Order By: Relevance
“…It has been shown that sustained peripheral drive from TrPs can evoke central sensitization in healthy subjects [14,15]. The intensity of the peripheral drives, as represented by an increasing number of active trigger points, is known to be increased in patients with frequent episodic TTH and chronic TTH [7,9,16] and hence drive the central sensitization [17].…”
Section: Search Criteria Tth Classifications and Limitationsmentioning
confidence: 99%
“…It has been shown that sustained peripheral drive from TrPs can evoke central sensitization in healthy subjects [14,15]. The intensity of the peripheral drives, as represented by an increasing number of active trigger points, is known to be increased in patients with frequent episodic TTH and chronic TTH [7,9,16] and hence drive the central sensitization [17].…”
Section: Search Criteria Tth Classifications and Limitationsmentioning
confidence: 99%
“…Watson and Drummond assessed the effects of sustained pressure on the atlanto-occipital segments and C2-3 zygapophyseal joints to relieve migraines 36 . In addition, several studies have reported that myofascial trigger points could reproduce migraine symptoms 37,38 , Moreover, an increasing amount of evidence shows that dyscoordination between the dorsal horns of the upper cervical spinal cord and trigeminal nucleus caudalis may induce cervicogenic headaches. The prolonged irritated inputs implicate in the pain processing through trigeminovascular system, which can provoke and worsen the symptoms of migraine 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The simplest of literature searches establishes a list of potential underlying causes of headache that is truly a litany of tribulation. The role of the trigemino-cervical reflex is well established [31,32] with the literature reporting that as much as 47% of the global population suffer with headache of which some 15 -20% are described as cervicogenic [33]. Thoracic outlet syndrome and in particular its variant of neurological thoracic outlet syndrome presents yet another clinical syndrome whose basis can frequently be related to or associated with sustained aberrant patterns of muscle tonicity, with manual therapy and management providing a first line of intervention.…”
Section: Discussionmentioning
confidence: 99%